Training of Cash Waqf Management on Da'i and Mubaligh - Soediro, Achmad; Kusumawardani, Media; Farhan, Muhammad; Adhitama, Fardinant; Yusrianti, Hasni; Patmawati, Patmawati; Budiman, Anton Indra (Faculty of Economics, Universitas Sriwijaya, 2022)
Community Service Implementation Activities with the theme